Sharing the Lived Experiences of Women in Academia by Remembering, Reclaiming and Retelling Stories of the Feminist Imaginaries - Hayward, Bev (International Journal for Talent Development and Creativity)

(untitled) (International Centre for Innovation in Education/Lost Prizes International, 2024)
Feminist Imaginaries are psychological and social spaces where creative possibilities are overflowing. They facilitate new ways of being, new ways of knowing and new ways of knowledge creation. This paper embraces a decolonial and feminist approach to storytelling, remembering, reclaiming and retelling; telling the stories of a band of wandering women, journeying to the psychosocial spaces of the Imaginary. Drawing upon a feminist theoretical tapestry, creative writing methods and autoethnographic approaches, the story is an example of the possibilities for Feminist Imaginaries in academic research. Many female students I have encountered naively believe they have social justice and equality but the inequalities are hidden in low paid, part-time work and unpaid care. To explore patriarchy’s deceptive nature, reference is made to the canons of Western art and literature as spaces from which to depart. It is from this space and time of departure that our journeys to the Imaginaries begin. Our lived experiences as artists as educators makes our activism all the more urgent to care for racialised, working class and disabled students. Those experiences are illustrated in poetry and visually in an artwork created to accompany this paper entitled, Remember, shout her name, tell her-story. Furthermore, creative writing is a form of the Imaginary and is used to tell this tale. I suggest, by borrowing from Laurel Richardson, creative writing is a method of inquiry to learn about ourselves and our research. By writing into the topic, rather than reading around and then writing, the imagination can wander and wonder freely. I include a small demonstration of how this process might be performed. In this way the story is open-ended, to be continued, as so too the fight for social and gender justice must continue. Accordingly, I invite you, the reader, to remember your stories, reclaim, imagine them, document and share them.